PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP KINERJA PEGAWAI STUDY PADA KANTOR SEKRETARIAT DAERAH KABUPATEN PEKALONGAN - Rizki Amalia Mutiyah, 14.05.51.0144; Waruwu, Penunjang (Students' Journal of Economic and Management, 2018)
This study aims to determine and analyze the influence of leadership, Work Environment and Motivation on employee performance Regional Secretariat Office of Pekalongan Regency. The population in this study is the entire staff of the Regional Secretariat Office of Pekalongan Regency, with a sample size of 70 respondents. Sampling technique in this research is purposive sampling. The primary data collection method used is questionnaire and data analysis using multiple linear regresi model. The results of this study indicate that leadership is negative and significant impact on employee performance while work environment and motivation have a positive and significant effect on employee performance. Keywords: Leadership, Work Rate, motivation, employee performance